PENGEMBANGAN KEBIJAKAN NASIONAL DALAM PENGELOLAAN KERUKUNAN - M. Ridwan Lubis (Harmoni, 2016)
Indonesia, renown as a pluralistic society, cannot utilize its plurality as a cement of national unity in organizing national building without state intervention through national policy. Therefore, there is a need of a social engineering to encourage people to heal their traumatic experiences in the past. Conversely, the people as a citizen can enjoy plurality that can lead to accepting both advantages and disadvantages of plurality. In that regard, they can possess the capability of being tolerant in the life of harmony. Consequently, the government is required to develop a national policy on religious harmony. Up until now, the government pays less attention to developing a regulation on religious harmony. This is due to some factors as follows: religion is a private matter to God; religious harmony can lead to religious emotion which is less proportional, or religious harmony is the initiative of the people which is based on local wisdom. It is worth saying that local wisdom is related to agricultural society. In this industrial and post-industrial society, the government needs to formulate a new policy that can maintain the national unity of the republic of Indonesia.